The use of QbD for the development and validation of a stability-indicating RP-HPLC method for the quantitation of nevirapine in bulk, tablet and niosome formulations - Witika, Bwalya A.; Walker, Roderick B. (Frontiers in Analytical Science, 2026)
IntroductionA reversed-phase high-performance liquid chromatographic (RP-HPLC) method was developed and validated for the quantitation of nevirapine (NVP) in bulk drug, commercial tablets, and niosome formulations using an Analytical Quality by Design (AQbD) approach.MethodsCritical analytical attributes and method parameters were identified and optimized using a Central Composite Design (CCD), with the retention time and resolution between NVP and internal standard carbamazepine as key responses. Chromatographic separation was achieved on a C18 column using an isocratic mobile phase of water and acetonitrile (57.5:42.5 v/v), a 1.0 mL/min flow rate, and detection at 280 nm. The method was validated per ICH Q2 (R1) guidelines for all parameters including repeatability, intermediate precision, accuracy (recovery/bias), and robustness, in addition to specificity, linearity, LOD and LOQ.Results and DiscussionThe method demonstrated specificity, linearity (0.5–200 μg/mL), a detection limit of 0.033 μg/mL, and quantification limit of 0.5 μg/mL. The method was precise, accurate, and robust. Stress studies suggested stability-indicating performance under the tested conditions with no observed interference at the analyte retention time at 280 nm. Application to commercial and in-house formulations confirmed its suitability for routine analysis. This work highlights the value of AQbD in developing cost-effective, high-performing analytical methods for pharmaceutical analysis.